The Ethical and Civic Dimension of Service Learning: A Model for its Institutionalization in Higher Education - Zayas Latorre, Belén; Gozálvez Pérez, Vicent; Gracia Calandín, Javier (Revista Complutense de Educación, 2018)
This article reflects on the ethical and civic value of the Service Learning projects, from a bibliographic review process, but also from an own foundation based on a hermeneutical analysis of this teaching-learning methodology. It is concluded that the Service Learning projects contribute to a practical synthesis between the ethics of care and that of justice, and contributes to a new definition of the concept of education, while those projects encourage meaningful learning and ethical and civic dimension of educational processes, according with proposals for human development and education understood as a common good from international organizations such as Unesco. After the theoretical foundation, we present a case of the institutionalization of Service Learning in Higher Education (Universitat de València), from the reconsideration of the university as a public space committed to the professional ethics and university social responsibility.
Keywords: learning; social commitment; professional ethics; university